Analisis Kolam Olak Bendungan Leuwikeris Kabupaten Ciamis-Tasikmalaya - Komalasari, Amelia Citra Mulya; Permana, Sulwan (Jurnal Konstruksi, 2024)
The Leuwikeris Dam is a dam built in two districts, namely Ciamis Regency and Tasikmalaya Regency. One of the structures of the dam is a stilling pond. Stilling ponds are built to reduce the energy contained in the flow by utilizing hydraulic jumps from a high-speed flow. The type of stilling pond at the Leuwikeris Dam is type USBR II which has a Froude number value of more than 4.5 and a discharge of more than 60mÂ³/second. The research carried out this time calculated the amount of energy loss in the stilling pond of the Leuwikeris Dam with the USBR II stilling pond type. In finding the value of energy loss, the discharge of the Leuwikeris Dam is needed using modeling. Discharge modeling uses the NRECA method by calibrating with existing discharge, namely the discharge in Cirahong. Discharge modeling is also used with normal distribution method calculations, log normal, gumbel and log pearson type III. The results of these calculations are an NSE value of 0.756 in modeling discharge using the NRECA method and calibrated with the Cirahong discharge for 5 years and the amount of energy lost in the stilling pond of 4.78 meters.